Conventional Vs. Islamic Finance: the Impact of Ramadan Upon Sharia-compliant Markets - Mitchell, Matthew C.; Rafi, Muhamad Iqbal Mohd; Severe, Sean; Kappen, Jeffrey (Organizations and Markets in Emerging Economies, 2014)
The Islamic financial industry is growing at a rate 50% faster than that of conventional banking and is expected to be worth USD 2.1 trillion by the end of 2014. This rapid growth and institutionalization of an alternative financial market highlights a growing need to further investigate Sharia-compliant markets and how they compare with their conventional market counterparts. This paper investigates this broad relationship by focusing on the effects of Ramadan upon the performance of Sharia-compliant financial instruments. Specifically, we utilize an event-study methodology to compare the performance of Sharia-compliant stocks to their conventional counterparts across a large sample of countries and regions. We find strong evidence for a significant Ramadan effect within Muslim majority countries and regions. The effect is strongest in the days leading up to Ramadan, and also around the beginning of Ramadan’s third Ashra on the 20th day. This timing reflects the mental, emotional and practical preparations that individuals go through during the course of the month-long observance. These results are not consistent with traditional economic expectations and therefore reflect the unique socially-embedded nature of this emerging and religiously inspired financial system.